Evidence of fast neutron detection capability of the CLLB scintillation detector. (January 2023) - Pino, Felix; Polo, Matteo; Delgado, Jessica C.; Mantovani, Giorgia; Carturan, Sara Maria; Fabris, Daniela; Brunelli, Davide; Pancheri, Lucio; Quaranta, Alberto; Moretto, Sandra
Abstract: For the first time we report the ability of the CLLB scintillator to detect and discriminate fast neutrons (2–10 MeV energy range) from gamma-rays and thermal neutrons, using a digital pulse shape discrimination technique. Firstly, we conducted measurements in single mode with an Am–Be source, unshielded and shielded, and we tagged a new cluster of events as the fast neutron-induced zone. The Figure of Merit obtained for the fast neutron/gamma discrimination was 1.1. Then, in order to better characterize these new cluster of events induced by fast neutrons, we conducted measurements in coincidence mode. We used a mono-energetic pulsed neutron source, at the Van de Graaff accelerator facility at the Legnaro National Laboratories (INFN-LNL, Legnaro-Italy), and also, a continuous neutron spectrum (using a 252 Cf source). Combining all experimental results with a Monte Carlo model of the CLLB detector, built using the GEANT4 tool kit, it was possible to obtain the light output function of 7 Li ions in the CLLB crystal (dL/dE = κ ; κ = 0.36 ± 0.02). Moreover, the intrinsic fast neutron efficiency was modeled by Monte Carlo, obtaining similar values 1.5%–2% for neutrons between 2 MeV and 10 MeV. Finally, an application of this new feature, in the field of nuclear security and nuclear safeguards, is given. Highlights: Fast neutron detection with a CLLB scintillation detector. Fast neutron/gamma-rays/thermal neutrons discrimination by applying digital pulse shape discrimination technique. Light output of Li ions in the CLLB scintillator. Recognition of neutron sources.